2022
DOI: 10.1242/jcs.259743
|View full text |Cite
|
Sign up to set email alerts
|

Vps68 cooperates with ESCRT-III in intraluminal vesicle formation

Abstract: The endosomal sorting complex required for transport (ESCRT)-III mediates budding and abscission of intraluminal vesicles (ILVs) into multivesicular endosomes. To further define the role of the ESCRT-III associated protein Mos10/Vps60 in ILV formation, we screened for new interaction partners by SILAC/MS. Here we focused on the newly identified interaction partner Vps68. Our data suggest that Vps68 cooperates with ESCRT-III in ILV formation. The deletion of VPS68 caused a sorting defect similar to the SNF7 del… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 44 publications
2
12
0
Order By: Relevance
“…The short-lived endocytic cargo protein Ste6 is transported to the yeast vacuole for degradation via the multivesicular body pathway (Kölling and Hollenberg, 1994). As described before, Ste6 is stabilized in the ∆vps68 mutant (Alsleben and Kölling, 2022). We now took a closer look at the kinetics of Ste6 degradation using a gal-depletion experiment.…”
Section: Kinetics Of Ste6 Turnover In the Vps68 Deletion Mutantmentioning
confidence: 96%
See 4 more Smart Citations
“…The short-lived endocytic cargo protein Ste6 is transported to the yeast vacuole for degradation via the multivesicular body pathway (Kölling and Hollenberg, 1994). As described before, Ste6 is stabilized in the ∆vps68 mutant (Alsleben and Kölling, 2022). We now took a closer look at the kinetics of Ste6 degradation using a gal-depletion experiment.…”
Section: Kinetics Of Ste6 Turnover In the Vps68 Deletion Mutantmentioning
confidence: 96%
“…In our previous study we identified Vps68 as an interaction partner of ESCRT-III (Alsleben and Kölling, 2022). Since Vps68 forms a complex with Vps55 (Schluter et al, 2008), we were interested to see, if Vps55 as well associates with ESCRT-III.…”
Section: Vps55 Interacts With Escrt-iiimentioning
confidence: 99%
See 3 more Smart Citations